Efficacy and safety of electroacupuncture on treating depression-related insomnia: a study protocol for a multicentre randomised controlled trial - Yin, Xuan (BMJ Open, 2019)
INTRODUCTION: Sleep disorders including insomnia occur frequently in depressive patients. Acupuncture is a widely recognised therapy to treat depression and sleep disorders in clinical practice. This multicentre randomised controlled trial (RCT) is aimed to investigate the efficacy and safety of electroacupuncture (EA) in the treatment of depression patients with insomnia. METHODS AND ANALYSIS: We describe a protocol for a multicentre RCT. A total of 270 eligible patients in three different healthcare centres in Shanghai will be randomly assigned to one of these three groups: treatment group (EA + standard care), control A group (sham electroacupuncture + standard care) and control B group (standard care). Treatment will be given three times per week for 8 consecutive weeks. The primary outcome is the Pittsburgh Sleep Quality Index. The secondary outcomes are sleep parameters recorded in the actigraphy, Hamilton Rating Scale for Depression score and Self-rating Anxiety Scale score. Daily dose of patients’ antidepressant and sedative-hypnotic medication will be recorded in the dairy. All adverse effects will be assessed by the Treatment Emergent Symptom Scale. Outcomes will be evaluated at baseline, 4 weeks post-treatment and 8 weeks post-treatment, as well as at 1-month, 3-month and 6-month follow-up. ETHICS AND DISSEMINATION: The trial has been approved by the Ethics Committee of Shanghai Municipal Hospital of Traditional Chinese Medicine (2017SHL-KY-04). Written informed consent will be obtained from all participants. The results of this study will be published in peer-reviewed journals or presented at academic conferences. TRIAL REGISTRATION NUMBER: NCT03122080; Pre-results.